Craniofacial and neurological manifestations in patients with Guillain-Barré Syndrome - Rubén Chumpitaz-Durand; Freddy Manayay (Universidad de Concepción., 2021)
Introducción: Among the broad range of symptoms of the Guillain-Barré Syndrome (GBS), patients can present craniofacial manifestations. Consequently, the participation of the dental surgeon in the evaluation of the stomatognathic system using a multidisciplinary approach model is very important. Objective: To identify the craniofacial and neurological manifestations of the Guillain-Barré Syndrome in patients from three hospitals in the district of Lambayeque, Peru, in 2019. Material and Methods: A descriptive, prospective, and cross-sectional study was carried out in 59 patients diagnosed with GBS by means of a clinical evaluation carried out by previously calibrated neurologists (k=0.911). Additionally, an oral evaluation of the oral hygiene index, the periodontal status, and the oral pH was carried out. Data were processed using frequency distribution tables. Results: 44.07% of the patients presented at least one functional alteration, such as unilateral limitation for facial expressions (25.42%), dysphagia (18.64%), alteration in phonation (11.86%), and loss of the sense of taste (6.78%), showing involvement of the corresponding cranial nerves. In addition, unfavorable conditions oforal hygiene and acid pH were observed in some cases, which proved adverse for the periodontal structures of the patients. Conclusion: The study found craniofacial manifestations of GBS, such as cases of unilateral facial palsy, dysphagia, difficulty in phonation, and loss of the sense of taste, due to the alteration of the cranial nerves that command these functions. In addition, poor oral hygiene, and the presence of acidic pH in some patients created an adverse environment for the integrity of the periodontal structures.